MENENTUKAN MENENTUKAN PH TANAH DI LAHAN PESISIR PANTAI CERIMIN KABUPATEN SERDANG BERDAGAI - Rahmat Dwi Prasetyo; Rizky Surya Panca; Nazril Ilham Tanjung; Kurniawan; Muhammad Adam Setiawan (PUCUK : Jurnal Ilmu Tanaman, 2025)
Coastal land plays an important role in supporting agricultural and fisheries activities, but often faces less than ideal soil, one of which is soil (pH). As part of sustainable land management, this study attempts to determine the nature of soil pH in coastal areas in Pantai Cermin District, Serdang Bedagai Regency, North Sumatra. In coastal areas, sampling was carried out at several locations with depths of 0–20 cm and 20–40 cm. then analyzed in the laboratory using a 1:1, 1:2.5 and 1N KCl ratio of 2.5 and electrometry to determine the pH value. The results of the study according to location have a soil pH ranging from acidic (pH 4.3 - 6.1), which is caused by the influence of natural processes such as climate, biology, sea air, and high organic matter content. Several locations show indications of active acid sulfate soil which has the potential to be detrimental if not managed properly. Understanding these pH characteristics is crucial as an initial step in selecting the right commodity, as well as for implementing improvements such as lime. the right chemicals and to make improvements such as lime. Therefore, knowledge about the pH of the air in Pantai Cermin Pesisir is very important to increase community productivity.